The religious and spiritual life of the Jews of Medina - Mazuz, Haggai, 1980- (The Brill Reference Library of Judaism, 2014)
In The Religious and Spiritual Life of the Jews of Medina Haggai Mazuz offers an account of the halakhic character of the Jewish community of Medina in the seventh century CE. Making use of a unique methodology of comparison between Islamic and Jewish sources, Mazuz convincingly argues that the Jews of Medina were Talmudic-Rabbinic Jews in almost every respect. Their sages believed in using homiletic interpretation of the Scriptures, as did the sages of the Talmud. On many halakhic issues, their observations were identical to those of the Talmudic sages. In addition, they held Rabbinic beliefs, sayings and motifs derived from the Midrashic literature.